Enhancing Corrosion Resistance and Structural Properties of Ni-TiO2 Composite Coatings: The Impact of SDS Surfactant (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Ni-TiO2 composite coatings are promising materials for enhancing the corrosion resistance and structural properties of steel substrates in various industrial applications. Corrosion remains a major issue for steel components, prompting the need for effective protective coatings. This study investigates the influence of sodium dodecyl sulfate (SDS) surfactant on the structural, electrochemical, mechanical, and morphological properties of Ni-TiO2 composite coatings electrodeposited on BS2 steel. The coatings were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), microhardness testing, and electrochemical techniques, including potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The results show that SDS incorporation led to an increase in the crystallite size of the coatings, from 35.92 nm to 80.82 nm, and a significant enhancement in the relative texture coefficient (RTC) along the (200) plane (88.09%). SEM analysis revealed a more compact and uniform surface morphology, with SDS reducing surface porosity from 8.23 × 10-3% to 2.20 × 10-6%. Electrochemical measurements demonstrated a substantial improvement in corrosion resistance, with charge transfer resistance (Rct) increasing from 5.17 kΩ.cm2 to 312.65 kΩ.cm2 and polarization resistance (Rp) rising from 2.5 kΩ.cm2 to 176.38 kΩ.cm2. The microhardness of the coatings decreased slightly from 256.26 kgf.mm-2 to 217.22 kgf.mm⁻², indicating a trade-off between mechanical strength and enhanced corrosion protection. These findings highlight the potential of SDS as a valuable additive for optimizing Ni-TiO2 composite coatings, although further research is needed to explore the impact of SDS concentration, long-term durability, and the performance of these coatings in more aggressive environments.
Keywords: Ni-TiO2; SDS; Corrosion Resistance; Relative Texture Coefficient; Porosity Reduction